EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN MEDIA PUZZLE PETA TERHADAP HASIL BELAJAR LETAK GEOGRAFIS INDONESIA SISWA KELAS V: Penelitian Hasil Pembelajaran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the Project Based Learning (PjBL) model assisted by map puzzle media in improving student learning outcomes on the subject of Indonesia's geographical location. This quantitative study used a pre-experimental method with a One Group Pretest–Posttest design involving 28 fifth-grade students at MIS Al-Misbah. Data were collected through pretest and posttest consisting of multiple-choice and essay questions that had been tested for validity and reliability. Data analysis used descriptive statistics, Kolmogorov–Smirnov and Shapiro–Wilk normality tests, paired sample t-tests, and N-Gain tests. The results showed that the pretest and posttest data were normally distributed. The paired sample t-test showed a significant increase in learning outcomes (t = 12.214; p = 0.000 < 0.05), with the average score increasing from 47.26 to 75.86. The N-Gain value of 0.46 was in the moderate category, indicating that the use of map puzzle media was effective in helping students understand spatial concepts through visual and manipulative learning experiences. These results confirm that the PjBL model assisted by map puzzle media is able to make abstract geographical concepts more concrete, meaningful, and easier to understand for elementary school students.